Association between maternal exposure to particulate matter and premature birth - Lima,Thaiza Agostini Córdoba de (2014)
The objective of this time-series study carried out in São José dos Campos, a southeastern Brazilian city, between 01.01.2005 and 31.12.2009, was to estimate the role of maternal exposure to air pollutants and preterm births. Preterm newborns of mothers aged between 18 and 34 years, with at least eight years of schooling, singleton pregnancies and whose delivery was vaginal were included in the study. Logistic regression was used to estimate the role of particulate matter, ozone and sulfur dioxide on preterm delivery with lags of zero up to 30 days. Exposure to particulate matter was associated significantly with preterm newborns in lags of 0, 1 and 3 days; but no association was found between cumulative maternal exposure in lags of 7, 15 and 30 days and the outcome. Maternal exposure to particulate matter therefore has an acute effect on preterm births in a medium-sized Brazilian town.